2021
DOI: 10.3390/coatings12010016
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Flow Control in Cavity with Cold Circular Cylinder Placed in Non-Newtonian Fluid by Performing Finite Element Simulations

Abstract: A study on strategies regarding advancement in heat transfer characteristics in two-dimensional closed domains by placing cold cylinders is conducted. This effort is undertaken due to the fact that active and passive control in heat transmission is connected with provision of temperature differences at different locations of enclosures. Based on the experiments, researchers have concluded that placement of cold cylinder in non-uniformly distributed heat in a cavity is the most effective technique to enrich hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In terms of solving PDEs, Stevenson et al (2020) have attempted to use the finite element method to analyze parabolic PDE [35], while Metzger (2021) have used FEM to solve 4th-order PDE, so as to solve the liquid crystal flow characteristics in liquid crystal flow guides [36]. In describing the solution of PDE of non-Newtonian fluid, Memon et al (2021) have used FEM simulate the heat transfer effect of non-Newtonian power law fluid on the surface of the end of a cylinder channel containing a mesh screen, and have pointed out that the heat transfer increases with the power exponent of non-Newtonian fluid [37]; Bilal et al (2022) and Nawaz et al (2022) have also studied the heat transfer characteristics of non-Newtonian fluid, and have used FEM to quantitatively solve the heat transfer characteristics of viscous fluid in different spaces and material environments [38][39]; Hou et al (2022) and Kune et al (2022) have discussed the properties of non-Newtonian fluid under the influence of Soret and Dufour effects, and have solved the heat and mass transfer characteristics of fluids with different properties under chemical reaction using FEM [40][41]; Omri et al (2022) have used the generalized FEM to discretize PDE so as to solve the convection heat transfer effect of non-Newtonian mixed nano fluid in the 3layer square cavity, and have reasonably approximated the temperature, speed and pressure of the fluid [42].…”
Section: Solving Pdes Based On Femmentioning
confidence: 99%
“…In terms of solving PDEs, Stevenson et al (2020) have attempted to use the finite element method to analyze parabolic PDE [35], while Metzger (2021) have used FEM to solve 4th-order PDE, so as to solve the liquid crystal flow characteristics in liquid crystal flow guides [36]. In describing the solution of PDE of non-Newtonian fluid, Memon et al (2021) have used FEM simulate the heat transfer effect of non-Newtonian power law fluid on the surface of the end of a cylinder channel containing a mesh screen, and have pointed out that the heat transfer increases with the power exponent of non-Newtonian fluid [37]; Bilal et al (2022) and Nawaz et al (2022) have also studied the heat transfer characteristics of non-Newtonian fluid, and have used FEM to quantitatively solve the heat transfer characteristics of viscous fluid in different spaces and material environments [38][39]; Hou et al (2022) and Kune et al (2022) have discussed the properties of non-Newtonian fluid under the influence of Soret and Dufour effects, and have solved the heat and mass transfer characteristics of fluids with different properties under chemical reaction using FEM [40][41]; Omri et al (2022) have used the generalized FEM to discretize PDE so as to solve the convection heat transfer effect of non-Newtonian mixed nano fluid in the 3layer square cavity, and have reasonably approximated the temperature, speed and pressure of the fluid [42].…”
Section: Solving Pdes Based On Femmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Bilal et al studied heat and flow control in a cavity. [10][11][12][13][14][15] Guerrero et al [16][17][18] studied the analysis of the heat transfer form of convection in a porous environment. Moftakhari et al 19 inquired about the heat transfer form of radiation in a triangular environment.…”
Section: Introductionmentioning
confidence: 99%
“…This research reported that the heat transport and momentum of base-fluid improved by the inclusion of Zinc-Nickel-ferrite particles. Followed by Bilal et al 10,11 extended the study on Newtonian and non-Newtonian nanofluid. The presence of Soret phenomenon improved the concentration while reduced in temperature is examined in these studies.…”
Section: Introductionmentioning
confidence: 99%